Return on Assets, Return on Equity, dan Net Profit Margin terhadap Pertumbuhan Laba - Rendi Gunawan Mahendra; Dian Hakip Nurdiansyah (IPM2KPE, 2022)
This research was conducted with the aim to determine the effect of Gross Return on Assets, Return on Equity, and Net Profit Margin partially or simultaneously on profit growth in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The research method used is descriptive verification. The technique used to determine the sample in this study was purposive sampling and obtained 10 companies during 5 years of research. The results showed that the calculated F value was 34.684, which was greater than the F table value of 2.81. Then a significance value of 0.000 > 0.05 is generated. Conclusion, a) net profit margin partially has a significant effect on the profit growth of registered pharmaceutical sub-sector companies in the study period. Meanwhile, return on assets and return on equity have a significant negative effect on research; b) return on assets, return on equity and net profit margin simultaneously influence the capital structure of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the study period. Keywords: Growth of Earnings, Net Profit Margin, Return on Assets, Return on Equity